Activating the Climate Child Imaginary: Intergenerational Collaboration as a Long-term Strategy for Climate Justice Education - David Rousell; Finn Ball; Riley Ball; Kairo Byrne; Amy Cutter-Mackenzie-Knowles; Jasmyne Foster; Annette Gough; Sam Lucena; Netta Maiava; Eve Mayes (Australian Journal of Environmental Education)
This article explores the potentials of intergenerational collaboration as a long-term research strategy for shifting social and political imaginaries around climate change. It brings together academics and youth researchers who began working together on the Climate Change and Me project in 2014, along with colleagues who joined them for a public panel, book launch and exhibition ten years later. Climate Change and Me was the first large-scale study of climate change education applying a child- and youth-framed methodology, and has led to numerous exhibitions, curriculum resources, digital platforms, and publications co-created with children and young people. This article gives voice to young people’s reflections on the impact of their involvement with this project a decade on, drawing on the transcript of a public panel conversation at the Design Hub Gallery in Naarm (Melbourne). It explores how young people’s early experiences as child researchers have intersected with political, social and educational change across time, while opening new conversations with intergenerational colleagues working in related areas of climate justice education, activism and research.